Changing distribution of norovirus genotypes and genetic analysis of recombinant GIIb among infants and children with diarrhea in Japan - Tung Gia Phan (2018)
A total of 402 fecal specimens collected during July 2003-June 2004 from infants and children with acute gastroenteritis, encompassing five localities (Maizuru, Tokyo, Sapporo, Saga, and Osaka) of Japan, were tested for the presence of norovirus by RT-PCR. It was found that 58 (14.4%) fecal specimens were positive for norovirus. Norovirus infection was detected throughout the year with the highest prevalence in December. Norovirus GII was the most predominant genogroup (98.3%; 57 of 58). The genotypes detected in this study were GI/4, GII/2, GII/3, GII/4, and GII/6. Of these, NoV GII/3 (known as the Arg320 virus cluster) was the most predominant genotype (43.9%), followed by NoV GII/4 (the Lordsdale virus cluster; 35.1%) and others. Two norovirus strains clustered with a "new variant designated GIIb" and a "new variant of GII/4" were found circulating in Japan for the first time. It was interesting to note that NoV GIIb and NoV GII/3 appeared to be the recombinant strains and the recombination site was demonstrated at the overlap of ORF1 and ORF2. The majority (96%) of the dominant norovirus strains were identified as the recombination of GII/3 capsid and GII/12 polymerase. The recombination in the NoV GIIb capsid gene at the breakpoint located at P1 domain was also identified. Obviously, NoV GIIb isolate in Japan had double recombination. This is the first report demonstrating the existence of different "new variants" co-circulating in Japanese infants and children with acute gastroenteritis. © 2006 Wiley-Liss, Inc.